Antibacterial Effect and Mode of Action of Flavonoids From Licorice Against Methicillin-Resistant Staphylococcus aureus - Wu, Shuai-Cheng; Yang, Zhi-Qiang; Liu, Fei; Peng, Wen-Jing; Qu, Shao-Qi; Li, Qian; Song, Xiang-Bin; Zhu, Kui; Shen, Jian-Zhong (Frontiers in Microbiology, 2019)
Staphylococcus aureus is a bacterial pathogen that causes food poisoning, various infections, and sepsis. Effective strategies and new drugs are needed to control S. aureus associated infections due to the emergence and rapid dissemination of antibiotic resistance. In the present study, the antibacterial activity, potential mode of action, and applications of flavonoids from licorice were investigated. Here, we showed that glabrol, licochalcone A, licochalcone C, and licochalcone E displayed high efficiency against methicillin-resistant Staphylococcus aureus (MRSA). Glabrol, licochalcone A, licochalcone C, and licochalcone E exhibited low cytotoxicity without hemolytic activity based on safety evaluation. Glabrol displayed rapid bactericidal activity with low levels of resistance development in vitro. Meanwhile, glabrol rapidly increased bacterial membrane permeability and dissipated the proton move force. Furthermore, we found that peptidoglycan, phosphatidylglycerol, and cardiolipin inhibited the antibacterial activity of glabrol. Molecular docking showed that glabrol binds to phosphatidylglycerol and cardiolipin through the formation of hydrogen bonds. Lastly, glabrol showed antibacterial activity against MRSA in both in vivo and in vitro models. Altogether, these results suggest that glabrol is a promising lead compound for the design of membrane-active antibacterial agents against MRSA and can be used as a disinfectant candidate as well.